ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN MODEL RISK-BASED BANK RATING (RBBR) (STUDI PADA PERBANKAN YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2011-2014) - Indah Permata Sari Reni Dahar (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
This study aims to find out How Banks using Model-Based Bank Risk Rating (RBBR) as seen from factors Risk Profile, Earnings and Capital at the Banking listing on the Indonesia Stock Exchange Period 2011-2014. This type of research used in this study was a descriptive study. The population in this study is the Banking Companies listed on the Indonesia Stock Exchange 2011-2014 period as many as 41 companies. Selection of the samples used in this research is by using purposive sampling method. The data used in this research is secondary data. The data collection technique is to use the techniques of documentation and literature. Data analysis technique used in this study is the Model Risk-Based Bank Rating (RBBR) by determining the Bank are classified into health ratings of banks.Results using the ratio of NPL, LDR, ROA, NIM, and showed that the CAR of the bank sampled in this study there is a bank that always produces predicate